The October Revolution and Bolshevik principles for solving the problem of National Autonomy - Guldana, Zhassulanovna Tarpanova (Axis – Vallás- és eszmetörténeti folyóirat, 2025)
The October Revolution of 1917 was one of the most significant and momentous events in the history of the 20th century, leading to the collapse of the Russian Empire and the creation of the first socialist state in the world. This event not only changed the political landscape of Russia, but also had a profound impact on international politics, inspiring subsequent revolutions and independence movements around the world.